Nilai-Nilai Kearifan Lokal Tradisi Lisan Guritan Keriye Rumbang Ngempang Lematang Suku Basemah, Pagaralam, Sumatera Selatan: Kajian Antropolinguistik: Local wisdom values of the oral tradition of guritan “Keriye Rumbang Ngempang Lematang” of the Basemah tribe, Pagaralam, South Sumatra: an anthropolinguistic study - Permatasari, Agmi Sinta Nanda (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
This study aims to determine the values ??of local wisdom contained in the guritan Keriye Rumbang Ngempang Lematang of the Basemah community, especially in Pagaralam City. The method used in studying the guritan Keriye Rumbang Ngempang Lematang is a qualitative method using an ethnographic approach according to Spradley. The research steps have been simplified as (1) determining informants; (2) interviewing informants; (3) making ethnographic notes; (4) asking descriptive questions; (5) conducting analysis of ethnographic interviews; (6) make component analysis (7) find cultural themes (8) write an ethnography. The simplification was carried out due to the limited resources, time, and cost of the researcher. Another reason that causes researchers to take this step is that existing circumstances such as this pandemic have only taken these eight steps without leaving the core of the twelve main steps. The data collection technique used is the interview technique. The results of the study show that the forms of local wisdom values ??contained in the guritan Keriye Rumbang Ngempang Lematang are local wisdom such as discipline, education, hard work, persistence, religion, mutual cooperation, local preservation, and cultural creativity.